2021
DOI: 10.20884/1.jap.2021.23.3.116
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc-Proteinate Supplementation on the In Vitro Digestibility and Ruminal Fermentation in Goat

Abstract: This study aimed primarily to investigate the effect of Zn-Proteinate (Zn-Prot) supplementation on in vitro rumen digestibility and rumen fermentation. This research used a completely randomized design with four treatments and four replicates. The experimental treatment was the supplementation of various levels of Zn-Prot (0; 12.5 ppm; 25 ppm, and 37.5 ppm) on a dry matter basis. Parameters determined were in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), partial volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Both inorganic Zn sources decreased the microbial protein synthesis. In a study assessing the effect of an organic source of Zn on rumen fermentation, it was found that the addition of 25 mg/kg DM of Zn as zinc proteinate (Zn-Prot) increased DM and organic matter digestibility, but did not affect acetate to propionate ration, nor CH4 concentration [80]. Table 6 compiles the effects on fermentation parameters of various inorganic and organic Zn sources.…”
Section: Trace Mineral Effects On Rumen Fermentation Parametersmentioning
confidence: 99%
“…Both inorganic Zn sources decreased the microbial protein synthesis. In a study assessing the effect of an organic source of Zn on rumen fermentation, it was found that the addition of 25 mg/kg DM of Zn as zinc proteinate (Zn-Prot) increased DM and organic matter digestibility, but did not affect acetate to propionate ration, nor CH4 concentration [80]. Table 6 compiles the effects on fermentation parameters of various inorganic and organic Zn sources.…”
Section: Trace Mineral Effects On Rumen Fermentation Parametersmentioning
confidence: 99%
“…Both inorganic Zn sources decreased the microbial protein synthesis. In a study assessing the effect of an organic source of Zn on rumen fermentation, it was found that the addition of 25 mg/kg DM of Zn as zinc proteinate (Zn-Prot) increased DM and organic matter digestibility but did not affect the acetate-to-propionate ratio nor CH 4 concentration [62]. Table 6 compiles the effects on fermentation parameters of various inorganic and organic Zn sources.…”
Section: Trace Mineral Effects On Rumen Fermentation Parametersmentioning
confidence: 99%